Joint interpretation of explosive and vibroseismic surveys on cold firn for the investigation of ice properties - Diez A.; Eisen O.; Hofstede C.; Bohleber P.; Polom U. (Annals of Glaciology, 2013)
Two seismic surveys were carried out on the high-altitude glacier saddle, Colle Gnifetti, Monte Rosa, Italy/Switzerland. Explosive and vibroseismic sources were tested to explore the best way to generate seismic waves to deduce shallow and intermediate properties (<100 m) of firn and ice. The explosive source (SISSY) excites strong surface and diving waves, degrading data quality for processing; no englacial reflections besides the noisy bed reflector are visible. However, the strong diving waves are analyzed to derive the density distribution of the firn pack, yielding results similar to a nearby ice core. The vibrator source (ElViS), used in both P-and SH-wave modes, produces detectable laterally coherent reflections within the firn and ice column.We compare these with ice-core and radar data. The SH-wave data are particularly useful in providing detailed, high-resolution information on firn and ice stratigraphy. Our analyses demonstrate the potential of seismic methods to determine physical properties of firn and ice, particularly density and potentially also crystal-orientation fabric.